A Model for Hypersensitive Airflow Sensor Concept / Mohamad Dzulhelmy Amari ...[et al.] - Amari, Mohamad Dzulhelmy; Che Abdullah, Sukarnur (Faculty of Mechanical Engineering Universiti Teknologi MARA (UiTM), 2017)
From an engineering standpoint, automated reaction from the system is most important in fulfilling the requirement of the intelligent control system. Nevertheless, many related studies regarding in developing the hardware of the system such as high sensitivity of the airflow modelling in detecting the changes either in user or the environment is very crucial in produce high quality airflow model. Hence, this research aims to develop preliminary design for the high sensitivity of the airflow in macrofluidic control in detecting the changes of the airflow movement based on relative velocity motion theory and describe the deformation behaviour of model structure in detecting the slight changes of the airflow field. The consideration of the new design should cover few parameters such as the deformation which covers speed range from 0 km/h to 110 km/h indicates higher sensitivity of airflow model and 360° of the upcoming airflow coverage. The design stage will be divided into multiple section which are the main structure, the tip and inner support structure (shape memory alloy). Integration of shape memory alloy material and consideration of different shape will be implemented to enhance the performance of the dynamic airflow model sensor. Nevertheless, the design provided in this paper can provide idea and fill the research gap in producing the airflow in macrofluidic model that can perform accurately in dynamic motion from the relative velocity.